PERKEMBANGAN INDEKS INKLUSIF KABUPATEN/KOTA DI PROVINSI NUSA TENGGARA TIMUR - Agung Putra (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
This study explore how inclusive economic growth has unfolded across 22 district and cities in East Nusa Tenggara, Indonesia. This study developed the Inclusive Index II, combining three key indicators: poverty rate, income inequality (gini ratio), and the Employment to Population (EPR). The index ranges from 0 to 1, with reduced poverty and improved labor participation, inequality remains a persistent issue widening in some regions. By applying the Klassen Typology, this study mapped each are into one of four categories: (I) Economically strong and inclusive, (II) Inclusive but economically lagging, (III) Lagging and non inclusive, and (IV) Economically strong but exclusive. Most districts fall into Quadrants II and III, showing that inclusive growth is far from evenly distributed. These insight highlight the urgent need for locally tailored, evidance based policies that do more than grow economies, they must also include and uplift the people within them.